Secure Sampled-Data Observer-Based Control for Wind Turbine Oscillation Under Cyber Attacks - Amini, Amir; Ghafouri, Mohsen; Mohammadi, Arash; Hou, Ming; Asif, Amir; Plataniotis, Konstantinos (IEEE transactions on smart grid, 2022)
Inspired by the recent surge of interest in security analysis of renewable energies, this article proposes a cyber resilient control framework for large-scale wind parks (WPs) against denial of service (DoS) and deception attacks. A detailed cyber-physical model for a doubly-fed induction generator (DFIG)-based WP is first developed. It is shown that the WP is subject to a stability issue known as the sub-synchronous interaction (SSI). Additionally, two cyber threats in the forms of DoS and deception attack attempt to destabilize the WP from the subsynchronous perspective. To stabilize the WP under the SSI phenomenon and these cyber attacks, an observer-based fuzzy control scheme is proposed which requires only periodic samples of the output. Using a looped-Lyapunov functional (LLF) method for stability analysis, the control and observer gains are computed from the solution of some linear matrix inequality (LMI) conditions. The proposed design framework allows including the desired level of cyber resilience to DoS and deception attacks for computing proper control and observer gains. The effectiveness of the proposed controller against the considered threats is demonstrated via electromagnetic transient (EMT) simulations performed using the EMTP-RV software and a co-simulation platform.